Pengaruh Terapi Musik dan Terapi Video Game terhadap Tingkat Nyeri Anak Usia Prasekolah yang Dilakukan Pemasangan Infus - Selvia Novitasari; Suhendar Sulaeman; Nyimas Heny Purwati (Journal of Telenursing (JOTING), 2019)
The purpose of this study was to determine the difference in the average level of pain in preschool children who were infused after being given music therapy and video game therapy at Bhayangkara Hospital TK III, Bengkulu City. This research is a quantitative research. This type of research is a quasy experimental research with a post-test only control group approach. The results showed that the level of pain after being given music therapy and video game therapy with a p value of 0.000. In conclusion, there is a difference in the average pain level of preschool children who have an IV after being given music therapy and video game therapy in the boys and girls group at Bhayangkara Hospital TK III, Bengkulu City. Keywords: Music, Preschool, Pain Level, Video Game